KNOWLEDGE, ATTITUDE AND PRACTICE OF YEMENI PHYSICIANS TOWARD PHARMACOVIGILANCE: A MIXED METHOD STUDY - Al-worafi, Yaser Mohammed (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: The objective of the current study was to investigate the physician's knowledge, attitude and practice towards pharmacovigilance. Methods: A mixed qualitative and quantitative method was conducted in this study using a face to face questionnaire among the physicians in the capital Sana'a, Yemen. Results: Of the 105 respondents (79 %) were male. Participants age mean was 35.55Â±4.45 y. Majority of physicians (73.3 %) had a moderate knowledge towards pharmacovigilance; (15.2 %) had a good knowledge and (11.4 %) had a poor knowledge. 35 (33.3 %) physicians were seen adverse drug reactions (ADRs) happened to their patients. Allergy was the most common ADRs. However, no ADR was reported. 66.7 % of physicians had a positive attitude towards pharmacovigilance. The most barriers reported by physicians were: lack of motivation and lack of knowledge about reporting system. Reported factors to encourage ADRs reporting were: attend courses or workshops; educational materials and simplification of reporting procedures. Conclusion: Majority of physicians in Sana'a, Yemen had moderate knowledge and postitive attitude towards pharmacovigilance. Educational and training programmes are the cornerstone of improving ADRs reporting in Yemen.Â 